The Charter and General Ordinances of the Town of Lexington, Virginia, at 87, ch. 42, § 1 (1892) - (:unkn) unknown (My University, 1867)
If any person carrying about his person, hid from common observation, any pistol, dirk, bowie-knife, razor, slung-shot, or any weapon of the like kind, he shall be fined not less than twenty dollars nor more than one hundred dollars; and any of such weapons mentioned shall be forfeited to the town. Nothing in this section shall apply to any officer of the town, county or state while in the discharge of his duty.
Keywords: CARRY - CONCEALED